PENGARUH PEMBERIAN SEDUHAN BAWANG PUTIH TERHADAP TEKANAN DARAH PADA LANSIA 60-74 TAHUN DENGAN HIPERTENSI DI POSBINDU MAWAR JOMBANG TANGERANG SELATAN PENGARUH PEMBERIAN SEDUHAN BAWANG PUTIH TERHADAP TEKANAN DARAH PADA LANSIA 60-74 TAHUN DENGAN HIPERTENSI DI POSBINDU MAWAR JOMBANG TANGERANG SELATAN - Riswahyuni Widhawati; Hadi Nugroho; Novi Nurul Fadillah (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Hypertension is a condition that increases one’s blood pressure above normal, resulting in increased pain and death rates. Hypertension can cause complications of other dangerous diseases if left without proper treatment. Treatment of hypertension can be done with pharmacological and non- pharmacological treatment. One of which non-pharmacological treatment is by giving garlic juice. The purpose of this study was to determine the effect of giving garlic juice on blood pressure in elderly with hypertension. This study uses a Quasy Experiment design with one group pretest posttest. This study has been conducted at Posbindu Mawar Jombang, south Tangerang. The population in this study is all elderly suffering hypertension desease. In this study the samples taken by quota sampling technique. Data analysed by T test Of Dependent. The result showed an average sistolic before giving the garlic juice is 158,00 with standard deviation 20,15 and an average diastolic before giving the garlic juice is 98,50 with standard deviation 8,12. The average sistolic after giving the garlic juice is 127,50 with standard deviation 7,16 and an average diastolic after giving the garlic juice is 85,50 with standard deviation 5,10. Theres is an effect of giving garlic juice on blood pressure in elderly with hypertension.